INTERCULTURAL THEOLOGICAL EDUCATION: TOWARDS A NEW FUTURE FOR FACULTIES OF THEOLOGY AT HIGHER EDUCATION INSTITUTIONS IN SOUTH AFRICA - Dames, Gordon Ernest (Scriptura, 2012)
This article is a first attempt in beating a new conceptual path for future and ongoing reflection and action in transforming faculties of theology at higher education institutions in South Africa. The following outline should guide us on our journey of discovery, reflection and participation. Firstly, the background and contextual picture of current transformational attempts at the University of the Free State (UFS) will be noted. Secondly, a local theoretical framework for intercultural theological formation is presented. Thirdly, an international theoretical framework for intercultural practices is provided. Fourthly, intercultural education will be viewed in the light of multicultural educational model. Fifthly, new methods of intercultural theological education will be proposed. The article will conclude with a few suggestions for future theological education